48XXYY Syndrome in an Adult with Type 2 Diabetes Mellitus, Unilateral Renal Aplasia, and Pigmentary Retinitis - Baha Zantour; Mohamed Habib Sfar; Samia Younes; Wafa Alaya; Mahdi Kamoun; Emna Mkaouar; Saida Jerbi (Case Reports in Medicine)
A 45-year-old male was referred for diabetes mellitus. Clinical examination found a family history of multiple precocious deaths, strong consanguinity, personal history of seizures during childhood, small testicles, small penis, sparse body hair, long arms and legs, dysmorphic features, mental retardation, dysarthria, tremor, and mild gait ataxia. Investigations found pigmentary retinitis, metabolic syndrome, unilateral renal aplasia, and hypergonadotropic hypogonadism, and ruled out mitochondrial cytopathy and leucodystrophy. Karyotype study showed a 48XXYY chromosomal type. Renal aplasia and pigmentary retinitis have not been described in 48XXYY patients. They may be related to the chromosomal sex aneuploidy, or caused by other genetic aberrations in light of the high consanguinity rate in the patient's family.